The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/eat.23536
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis of avoidant restrictive food intake disorder in the presence of gastrointestinal disorders: Opportunities to define shared mechanisms of symptom expression

Abstract: Objective Individuals with a gastrointestinal (GI) disorder often alter their diet to manage GI symptoms, adding complexity to understanding the diverse motivations contributing to food avoidance/restriction. When a GI disorder is present, the DSM‐5 states that Avoidant/Restrictive Food Intake Disorder (ARFID) can be diagnosed only when eating disturbance exceeds that expected. There is limited guidance to make this determination. This study attempts to address this gap by characterizing the presentation of AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…In addition to these results, one study from 2020 reported that over 60% of children with ARFID admitted to a paediatric hospital had some past history of GI problems (Tsang et al., 2020 ). These estimates, although different from each other, suggest that there might be an overlap between ARFID and GI problems, which could be important for understanding the aetiology of some presentations (Nicholas et al., 2021 ). The presence of GI symptoms together with ARFID should inform case formulation with assessment and intervention for GI symptoms being a clinical priority in this patient group (Boerner et al., 2021 ; Nicholas et al., 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to these results, one study from 2020 reported that over 60% of children with ARFID admitted to a paediatric hospital had some past history of GI problems (Tsang et al., 2020 ). These estimates, although different from each other, suggest that there might be an overlap between ARFID and GI problems, which could be important for understanding the aetiology of some presentations (Nicholas et al., 2021 ). The presence of GI symptoms together with ARFID should inform case formulation with assessment and intervention for GI symptoms being a clinical priority in this patient group (Boerner et al., 2021 ; Nicholas et al., 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…Both groups had similar frequencies of physical symptoms, though patients diagnosed with SSRD had more co-occurring medical conditions. The high proportion of patients with ARFID reporting GI symptoms (84%) may be relevant to understanding the underlying etiology of certain presentations of this diagnosis that may overlap with GI disorders, including central sensitization ( Sim et al, 2021 ) and interactions of altered gut physiology with symptom-related distress and fear-learning ( Nicholas et al, 2021 ; Wildes et al, 2021 ). However, it is also possible that some of the reported GI concerns were consequences of malnutrition, such as constipation, rather than an initiating factor for the eating disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Among those with DGBI, disordered eating patterns (such as food restriction, binge eating, purging) ranges from 5% to 44% 28 . More recently, the phenomenon of ARFID in DGBI has been recognized with cross-sectional and retrospective studies 4,10,11,29–36 …”
Section: The Relevance Of Arfid In Dgbismentioning
confidence: 99%
“…Differences in self-report frequencies may be due to varying cutoffs applied across studies on one ARFID screening questionnaire [the Nine-Item ARFID Screen (NIAS)], 38,39 as well as characteristics of the clinical populations. Finally, a cross-sectional self-report survey study found that among a community of self-identified “picky eater” adults who self-reported DGBI symptoms, 11% met the diagnostic criteria for ARFID 31 . To our knowledge, no study to date has investigated the frequency of ARFID in DGBI using semistructured or clinician interview (the gold standard for diagnosis of eating disorders), thus current frequency estimates are limited by the use of self-report surveys.…”
Section: The Relevance Of Arfid In Dgbismentioning
confidence: 99%